Risk factors and outcomes for delayed kidney graft function in simultaneous heart and kidney transplant recipients: A UNOS/OPTN database analysis. Issue 9 (11th February 2021) - Parajuli, Sandesh; Karim, Aos. S.; Muth, Brenda L.; Leverson, Glen.E.; Yang, Qiuyu; Dhingra, Ravi; Smith, Jason W.; Foley, David P.; Mandelbrot, Didier A.
Abstract : There are no prior studies assessing the risk factors and outcomes for kidney delayed graft function (K‐DGF) in simultaneous heart and kidney (SHK) transplant recipients. Using the OPTN/UNOS database, we sought to identify risk factors associated with the development of K‐DGF in this unique population, as well as outcomes associated with K‐DGF. A total of 1161 SHK transplanted between 1998 and 2018 were included in the analysis, of which 311 (27%) were in the K‐DGF (+) group and 850 in the K‐DGF (−) group. In the multivariable analysis, history of pretransplant dialysis (OR: 3.95; 95% CI: 2.94 to 5.29; p < .001) was significantly associated with the development of K‐DGF, as was donor death from cerebrovascular accident and longer cold ischemia time of either organ. SHK recipients with K‐DGF had increased mortality (HR: 1.99; 95% CI: 1.52 to 2.60; p < .001) and death censored kidney graft failure (HR: 3.51; 95% CI: 2.29 to 5.36; p < .001) in the multivariable analysis. Similar outcomes were obtained when limiting our study to 2008–2018. Similar to kidney‐only recipients, K‐DGF in SHK recipients is associated with worse outcomes. Careful matching of recipients and donors, as well as peri‐operative management, may help reduce the risk of K‐DGF and the associated detrimental effects. Abstract : Among the recipients of simultaneous heart and kidney transplants, pretransplant dialysis is associated with increased risk of kidney delayed graft function which, in turn, is associated with increased risk of kidney graft failure and patient mortality.